Persepsi Karyawan Front Office Department Hotel Terhadap Budaya Tipping - Calvin Mercy Ebenhaezer Watulingas; Vincentia Ratna Inggawati (Improvement: Jurnal Manajemen dan Bisnis, 2021)
Tipping is now a common thing for Indonesians, especially in the hospitality sector. In order to maintain the quality provided to remain good, adequate quality of human resources is needed. For employees who are seen to have provided satisfactory service, one form of consumer appreciation is to provide bonuses in the form of tips.This research is to see how employees perceive the tipping culture, which involves front office department employees and 4 consumers at 3-star hotels in East Surabaya. This study uses a descriptive approach with interviews as a data collection technique. Each hotel selected 3 employees and 2 consumers who represent the research subjects. The results showed that there were 2 tip distribution systems, namely no tip distribution (individual) and the same tip distribution (collective). However, the sharing of tips (individual) system often creates conflicts in its application, so it needs special attention from the hotel management. For employees who receive, Tips can increase motivation, rewards (personal achievements), volunteer money from guests, and additional salary for savings. Also that the tip is an appreciation of the attitude of employees who are polite, friendly, and responsive in dealing with consumer complaints staying at the hotelPemberian tip saat ini sudah merupakan hal yang umum dilakukan oleh masyarakat Indonesia terutama pada bidang perhotelan. Untuk menjaga kualitas layanan yang diberikan agar tetap baik, dibutuhkan kualitas sumber daya manusia yang memadai. Bagi karyawan yang dipandang telah memberikan layanan yang memuaskan, salah satu bentuk apresiasi konsumen adalah dengan memberikan bonus berupa tip.Penelitian ini untuk melihat bagaimana persepsi karyawan terhadap budaya tipping, yang melibatkan karyawan front office department serta konsumen di 4 hotel bintang III yang ada di Surabaya Timur. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan wawancara sebagai teknik pengambilan data. Dari masing-masing hotel dipilih 3 orang karyawan dan 2 orang konsumen yang mewakili subjek penelitian. Hasil penelitian menunjukkan bahwa terdapat 2 sistem pembagian tip yaitu no sharing of tips (individual) dan equal sharing of tips (kolektif).  Namun system sharing of tips (individual) sering menimbulkan konflik dalam penerapannya, sehingga perlu perhatian khusus dari pihak manajemen hotel. Bagi karyawan yang menerima, Tip mampu meningkatkan motivasi,  penghargaan (personal achievement), uang sukarela dari tamu (guess dicretion) dan tambahan gaji untuk tabungan. Juga ditemukan bahwa tip merupakan apresiasi dari  sikap karyawan yang sopan, ramah, dan cepat tanggap dalam mengatasi komplain konsumen yang menginap di HotelKeywords: Perception, Culture of Tipping, Front Office Department, Hotel